Parallel Synthesis of Poly(amino ether)-Templated Plasmonic Nanoparticles for Transgene Delivery - Ramos, James (American Chemical Society, 2014)
[Image: see text] Plasmonic nanoparticles have been increasingly investigated for numerous applications in medicine, sensing, and catalysis. In particular, gold nanoparticles have been investigated for separations, sensing, drug/nucleic acid delivery, and bioimaging. In addition, silver nanoparticles demonstrate antibacterial activity, resulting in potential application in treatments against microbial infections, burns, diabetic skin ulcers, and medical devices. Here, we describe the facile, parallel synthesis of both gold and silver nanoparticles using a small set of poly(amino ethers), or PAEs, derived from linear polyamines, under ambient conditions and in absence of additional reagents. The kinetics of nanoparticle formation were dependent on PAE concentration and chemical composition. In addition, yields were significantly greater in case of PAEs when compared to 25 kDa poly(ethylene imine), which was used as a standard catonic polymer. Ultraviolet radiation enhanced the kinetics and the yield of both gold and silver nanoparticles, likely by means of a coreduction effect. PAE-templated gold nanoparticles demonstrated the ability to deliver plasmid DNA, resulting in transgene expression, in 22Rv1 human prostate cancer and MB49 murine bladder cancer cell lines. Taken together, our results indicate that chemically diverse poly(amino ethers) can be employed for rapidly templating the formation of metal nanoparticles under ambient conditions. The simplicity of synthesis and chemical diversity make PAE-templated nanoparticles useful tools for several applications in biotechnology, including nucleic acid delivery.